The effect of Instagram influencers on intention to purchase among generation Z in Cape Town - Mxunyelwa, Ayabonga Siyamthanda (Cape Peninsula University of Technology, 2024)
The use of Instagram influencers has emerged as an essential strategy in digital marketing, with compelling evidence demonstrating a considerable impact on modifying consumer purchase intention. Despite the extensive use of the internet, additional academic research is required concerning how Instagram influencers affect the behaviour of young consumers. Instagram influencers are rapidly growing into a vital part of social media marketing strategies. The evolution of digital technology has resulted in diverse forms of marketing and endorsing, particularly through channels such as Instagram. The growing use of Instagram and its influencers in marketing demonstrates their substantial influence on customer behaviour intentions. Despite this, further research into the effects of Instagram influencers on customer intentions is needed. Generation Z is distinguished by its involvement in the digital space; they use Instagram as a platform for exchanging more information about current trends. Generation Z, as future digital decision-makers and customers, requires greater understanding to design effective marketing strategies. This study investigates the effects of Instagram influencers on Generation Z, specifically how influencer endorsements affect consumer purchase intentions in this cohort. Instagram influencers are used by marketers to enhance engagement and increase customer purchase intent. However, further information is required in African developing countries about how consumers perceive Instagram influencers. This study used the perceived usefulness, ease of use, and intention to purchase constructs from the technology acceptance model (TAM). The associations of the TAM constructs were assessed in relation to the source credibility model constructs, which included attractiveness, credibility, expertise, and trust. The study used structural equation modelling to examine the relationships between these constructs in terms of Instagram influencer marketing. The main aim of the study was to assess the influence of attractiveness, credibility, expertise, trust, perceived ease of use, and perceived usefulness on intention to purchase due to Instagram influencers among Generation Z in Cape Town, South Africa. The study also explored how age, gender, and educational level affect this cohort of consumers' intention to purchase due to social media influencer marketing. Additionally, this study sought to evaluate the methods by which Generation Z consumers' purchase intentions are influenced by influencers, time spent on Instagram, average spending, influencer types, Instagram's role in brand endorsements, frequency of Instagram use, and influencer purchase intentions. This study combined purposive and snowball non-probability sampling methods using a quantitative approach. A self-administered questionnaire was used to assess the effect of Instagram influencers on young consumers’ purchase intentions. The survey was distributed physically and also electronically through Google Forms at the Cape Peninsula University of Technology District Six campus and surrounding areas, as well as to the referrals emanating from the snowball sampling. Statistical Package for Social Science software was used to analyse the data that emanated from 1 881 respondents. The CPUT Business and Management Sciences Faculty Ethics Committee approved the study ethically, and all participants provided informed consent. The development of an updated TAM and source credibility models integrating Instagram influencers in digital marketing showed positive correlations between various influencer constructs (attractiveness, credibility, expertise, perceived ease of use, and perceived usefulness) and purchase intentions. The study also found that improved purchase intentions among Generation Z were associated with Instagram influencers with a higher number of followers, greater Instagram usage in terms of time and frequency, higher digital spending, and stronger behavioural purchase intentions. This analysis provides South African businesses with insightful information about methods to use Instagram influencers in digital marketing to connect with Generation Z, a group that aspires to companies that share their values. The study extends the body of knowledge on influencer marketing by determining the effects of Instagram influencers. The results highlight the significance of employing influencers who are attractive, credible, trustworthy, and considered to be experts by showing that influencer marketing favourably affects purchase intentions. Moreover, the perceived usefulness and ease of use of Instagram further increase its significance in interacting with younger consumers. By incorporating Instagram influencers into their marketing strategy and incorporating their credible endorsements, brands may increase consumer purchase intentions. This study contributes to the growing research on Instagram influencers as a method of digital marketing and provides innovative perspectives and a more comprehensive understanding of attitudes toward and usage of Instagram, in addition to the frequency of use of these influencers in the context of Generation Z consumer digital marketing. Through the extension of the TAM and the source credibility model, the results of the current research contribute to the body of literature, which indicates that the use of Instagram in social media positively influences several associations between perceived usefulness, expertise, trust, attractiveness, credibility, and ease of use. This study is important because it ensures that young consumer preferences are better understood and allows for the tailoring of future strategies to enhance the effectiveness of marketing strategies, enabling brands, organisations, marketers, and advertisers to reach this young cohort, as well as to gain a competitive advantage in the marketplace. The outcomes of the present research add to the current literature by highlighting Instagram as a significant channel for marketers to take into consideration when seeking to affect Generation Z's purchasing attitudes. Furthermore, when influencer marketing is used on digital shopping platforms, it becomes a strategic technique for increasing business revenues as well as for successfully influencing customer purchasing intentions.
Thesis (Master of Marketing)--Cape Peninsula University of Technology, 2024
Keywords: Attractiveness; Credibility; Expertise; Generation Z (Gen Z); Influencer; Instagram; Intention to purchase; Perceived ease of use; Perceived usefulness; Social media; Source credibility model; Technology Acceptance Model (TAM); Trust